Q: Simplify x plus 5 plus 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

1 x 4 + 2 x 5 4 + 10 14

13x+27=3x+32 Reorder 13x-3x=32-27 Simplify 10x=5 Simplify x=5/10 Simplify x=1/2 Answer

x2 + 4x = x(x+4)

x - 3x + 4 = 3 - 9 simplify -2x + 4 = -6 -4 -4 -2x = -10 /-2 /-2 x = 5

-1

Related questions

1 x 4 + 2 x 5 4 + 10 14

(x2 - x - 20) / (x2 + 8x + 16) = [(x - 5)(x + 4)] / (x + 4)2 = (x - 5) / (x + 4)

[(7+3)/(x+4)] / [(x-5)/(2-4)] =[(7+3)/(x+4)] * [(2-4)/(x-5)] =[10*(x-5)] / [-2*(x+4)] =-5*[(x-5)/(x+4)]

Assume the expression is:4/(x + 2) + 6/(x + 5)Simplify this expression by combining the expressions altogether. Let's go step by step.Step 1: Determine the LCD of the expression.The LCD of the expression is (x + 2)(x + 5). Multiply the top and bottom of each fractional expression by whatever factor the denominator is missing!4/(x + 2) * (x + 5)/(x + 5) + 6/(x + 5) * (x + 2)/(x + 2)Step 2: Combine the expression and simplify.(4(x + 5) + 6(x + 2))/((x + 2)(x + 5))= (4x + 20 + 6x + 12)/((x + 2)(x + 5))= (10x + 32)/((x + 2)(x + 5))

13x+27=3x+32 Reorder 13x-3x=32-27 Simplify 10x=5 Simplify x=5/10 Simplify x=1/2 Answer

x2 + 4x = x(x+4)

x - 3x + 4 = 3 - 9 simplify -2x + 4 = -6 -4 -4 -2x = -10 /-2 /-2 x = 5

The answer is 5x+3y. (5 xs and 3 ys)

-1

3 + x = 8 x = 5

Factor it out: (x+2) squared

3 * x + 4 + 2xMDAS rule:3x + 4 + 2x5x + 4